2003
DOI: 10.1159/000070227
|View full text |Cite
|
Sign up to set email alerts
|

A Plurihormonal TSH-Producing Pituitary Tumor of Monoclonal Origin in a Patient with Hypothyroidism

Abstract: Objective: A clinicopathological and clonal study of a pituitary tumor was made in a 26-year-old woman with chronic thyroiditis to differentiate TSH-producing adenoma from TSH hyperplasia. Methods: Tumor specimens were subjected to histopathological study and clonal analysis (HUMARA). Results: Immunohistochemical examination disclosed TSH-beta, PRL, GH, ACTH, FSH-beta, LH-beta, and alpha-subunit production in the adenoma cells. These heterogeneous phenotypes are characteristic of both thyrotroph hyperplasia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
1
12
0
3
Order By: Relevance
“…TSH-secreting adenomas have been reported in patients ranging from 8 to 84 years of age (most are in the 5th or 6th decade of life), with equal frequency in men and women, 3 which agrees with our findings. Similar to other reports, 21,34 one case was associated with previous Hashimoto's thyroiditis and hypothyroidism and one case was associated with multiple endocrine neoplasia Type 1.…”
Section: Clinical Characteristicssupporting
confidence: 89%
“…TSH-secreting adenomas have been reported in patients ranging from 8 to 84 years of age (most are in the 5th or 6th decade of life), with equal frequency in men and women, 3 which agrees with our findings. Similar to other reports, 21,34 one case was associated with previous Hashimoto's thyroiditis and hypothyroidism and one case was associated with multiple endocrine neoplasia Type 1.…”
Section: Clinical Characteristicssupporting
confidence: 89%
“…Autoimmune hypothyroidism may co-exist with TSHoma, but any causality is yet unclear (112,113,114). Pituitary hyperplasia from increased TSH production in hypothyroidism may in some rare cases mimic a macroadenoma (115).…”
Section: Concomitant Diseases In Association With Tshomasmentioning
confidence: 99%
“…It has been demonstrated that TSHomas are monoclonal in origin [15], thus suggesting that the development of TSHomas might be explained by the presence of a transforming event providing gain of proliferative function followed by secondary mutations or alterations favoring tumor progression [16]. However, to date, no mutations either in oncogenes commonly activated in human cancer (e.g.…”
Section: Introductionmentioning
confidence: 99%